J08 Effects of caffeine on early morning physical and cognitive performance - Chadwick, Michael (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Anaerobic and gross muscular performance is significantly greater in the evening that in the morning, due to the body clock and higher muscle and core temperatures in the evening compared to the morning (Ayala et al. 2021., Chron Int, 38, 1522-1536). However, little is known on the effect of caffeine supplementation on early morning gross muscular and cognitive performance, and whether this can mask the performance limitations imposed by the morning hours. Eight healthy, active male participants (mean ± SD: age, 21 ± 1 years; body mass, 78 ± 7 kg; stature, 178 ± 4 cm) volunteered and completed 2 familiarisation sessions and two experimental sessions. Experimental sessions 1) caffeine pill condition and 2) no pill condition was counterbalanced in order of administration (separated by >48h). The sessions began at 07:00h. During each session, intra-aural temperature was taken after participants had reclined for 30-min at the start of the protocol. Questionnaires were also provided to assess mood and sleep, then cognitive performance was assessed via the Stroop test. Agility was assessed using the Whitty SEM micrograte system, grip strength was measured using a hand grip dynamometer and finally 3x countermovement jumps and 3x squat jumps were recorded using a Jump mat. The aims of the study were to assess the effects of caffeine supplementation on 1) gross muscular and 2) cognitive assessments.